Updated geographical distribution of the family Barychelidae Simon, 1889 from Brazil (Araneae: Mygalomorphae) - Gonzalez Filho, Hector Manuel Osorio [UNESP]; Costa, Pedro Henrique Dias da Silva [UNESP]; De Paiva, Jean Martin Duarte; Guadanucci, José Paulo Leite [UNESP] (Boletim do Museu Paraense Emilio Goeldi, 2025)
As aranhas da família Barychelidae, grupo irmão de Theraphosidae, estão principalmente concentradas no Hemisfério Sul. Na região neotropical, Barychelidae é representada por cinco gêneros encontrados em Brasil, Colômbia, Cuba, Equador, Panamá, Peru e Venezuela. Aranhas Barychelidae são conhecidas pelo seu hábito sedentário, passando a maior parte de suas vidas em tocas construídas com um alçapão articulado, feito de seda e solo. Este hábito e a dificuldade de identificar e localizar suas tocas camufladas representam desafios na obtenção de espécimes, mascarando a real diversidade do grupo. O exame de vários espécies de diferentes coleções zoológicas nos permitiu expandir a distribuição geográfica de aranhas Barychelidae, acrescentando 95 novos registros. Adicionalmente aos dados geográficos de material de coleta, foi possível identificar 56 observações de aranhas Barychelidae no iNaturalist, 29 delas para locais não publicados, totalizando 124 novos registros no Brasil. Em geral, a distribuição geográfica expandida de Barychelidae no Brasil revelou uma notável diversidade, com inúmeras espécies cobrindo uma variedade de habitats. Este mapeamento da distribuição pode fornecer valiosas informações para o estudo da variação populacional e relações evolutivas, além de auxiliar em pesquisas biogeográficas da família Barychelidae. Spiders of the family Barychelidae, the sister group to Theraphosidae, are mainly concentrated in the Southern Hemisphere. In the Neotropical region, Barychelidae is represented by five genera found in Brazil, Colombia, Cuba, Ecuador, Panama, Peru and Venezuela. Barychelid spiders are known for their sedentary behavior, spending most of their lives in burrows constructed with a hinged trapdoor made of silk and soil. This habit and the difficulty in identifying and locating their camouflaged burrows, poses challenges to obtaining specimens thereby obscuring the group’s true diversity. Examination of numerous specimens from different zoological collections allowed us to expand the distribution of Barychelidae spiders adding 95 new records. In addition to geographic data from colleted material, we were able to find 56 iNaturalist observations of barychelid spiders, with 29 in unpublished locations, totaling 124 new records in Brazil. Overall, the expanded geographical distribution of Barychelidae spiders in Brazil has revealed remarkable diversity, with numerous species covering a variety of habitats. This distribution mapping can provide valuable information for the study of populations variation and evolutionary relationships and help in the biogeographical research of the family Barychelidae.